English - Abotsi, Benedict; English; English (Journal of Health Informatics in Africa, 2024)
Background and Purpose: Medical professionals keep a patient's medical record current using the Electronic Health Record System (EHRS), an electronic version of the document. It includes the crucial clinical and administrative information needed to manage the patient's treatment, such as demographics, issue notes, progress notes, prescriptions, vital signs, previous medical records, vaccination records, laboratory results, and radiological reports.Methods: The grounded theory methodology was used to review relevant literature and lay the groundwork for this investigation. Additionally, the information was gathered via a well-structured questionnaire distributed to medical professionals. The main objective of the study was made clear to the participants. The researchers distributed questionnaires to the individuals who provided healthcare using EHRS at their places of employment. Any queries the participants had regarding the questionnaire were allowed to be answered.Results: The main driving force behind this study was finding out what function AlphaChem Hospital's EHRS performs in delivering high-quality care. The study's key findings were that the EHRS helps the hospital by enhancing the accuracy of patient records, enabling the simultaneous care of multiple patients, streamlining appointment scheduling, and decreasing the time spent providing care while maintaining high user satisfaction. Frustrating factors include issues with lack of technical training, lack of technical support, and unstable internet connectivity.Conclusions: Most healthcare providers at AlphaChem Hospital were satisfied with the system and chose the electronic health record system over the paper-based one. However, there were some challenges with EHRS utilization. The report suggests that facility administrators properly orient all staff members on using the system. A facility that wants to gain a competitive edge must adopt, contribute to, and use an electronic health record system to manage health services.Keywords: Electronic Health Record System (EHRS), electronic medical record, healthcare, surgical, obstetrics